2007
DOI: 10.1016/j.jsb.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Reticulon 4a/NogoA locates to regions of high membrane curvature and may have a role in nuclear envelope growth

Abstract: Reticulon 4a (Rtn4a) is a membrane protein that shapes tubules of the endoplasmic reticulum (ER). The ER is attached to the nuclear envelope (NE) during interphase and has a role in post mitotic/meiotic NE reassembly. We speculated that Rtn4a has a role in NE dynamics. Using immuno-electron microscopy we found that Rtn4a is located at junctions between membranes in the cytoplasm, and between cytoplasmic membranes and the outer nuclear membrane in growing Xenopus oocyte nuclei. We found that during NE assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 37 publications
6
51
0
Order By: Relevance
“…In fact, Rtns are not only specifically localized to tubular ER domains but also to the edges of cisternae and edges of the fenestra found within cisternae (Fig. 1D,E) (Kiseleva et al 2007;Schuck et al 2009;Shibata et al 2010). Consistent with this localization, yeast cells in which Rtn/Yop1 have been deleted lack tubules but also contain expansive cisternae that are no longer fenestrated .…”
mentioning
confidence: 59%
“…In fact, Rtns are not only specifically localized to tubular ER domains but also to the edges of cisternae and edges of the fenestra found within cisternae (Fig. 1D,E) (Kiseleva et al 2007;Schuck et al 2009;Shibata et al 2010). Consistent with this localization, yeast cells in which Rtn/Yop1 have been deleted lack tubules but also contain expansive cisternae that are no longer fenestrated .…”
mentioning
confidence: 59%
“…Deletion of both RTN1 and YOP1, encoding two of the reticulons of S. cerevisiae, causes defects in nucleoporin localization and NPC distribution within the NE (10). In metazoan cells, reticulons are required for proper reassembly of the NE following mitosis (41,42). Using a Xenopus laevis in vitro system where de novo assembly of new NPCs takes place, Dawson et al (2009) showed that addition of an anti-reticulon antibody to the system led to a block in the assembly of new NPCs (10).…”
Section: Discussionmentioning
confidence: 99%
“…The ER exists as a continuous meshwork of membrane sheets and membrane tubules. Proteins known as reticulons cause tubule formation in the ER (Voeltz et al, 2006), and high levels of reticulons are inhibitory to nuclear growth, which suggests that the availability of membrane in the form of sheets can put an upper limit on nuclear size (Anderson and Hetzer, 2008;Kiseleva et al, 2007). Work in the Xenopus system has demonstrated a requirement for NPCs and nuclear import in nuclear growth after NE assembly (D'Angelo et al, 2006;Newport et al, 1990), which suggests that the import of one or more nuclear proteins contributes to sizing the nucleus.…”
Section: Factors That Affect Nuclear Volumementioning
confidence: 99%